Champions of the rule of law - Hostettler, John (Waterside Press, 2011)
An account of the lawyers who helped - over centuries - to develop and protect civil liberties, human rights and the Rule of Law. Also discusses breaches of the Rule of Law in modern cases and in response to terrorism.